TINGKAT PLOIDI PAKU SAYUR (Diplazium esculentum) PADA KETINGGIAN YANG BERBEDA DI GUNUNG SEMERU - Wulandari, Anggun; Rahmawati, Rina Dian (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
Polyploidy is a condition when the individual has more than two genomes, this polyploidy phenomenon is common in fern plants and one of the causes that is suspected to cause polyploidy events is cold temperatures. Therefore, this research aims to determine the level of ploidi fern vegetables (Diplazium esculentum) at different altitude in Semeru Mountain. This research is an experimental research using Completely Randomized Design (CRD). The object used is the Diplazium esculentum taken from different altitude (500 masl, 1500 masl, and 2500 masl) in Semeru Mountain. The next step is making the preparatory and chromosomal counts were then calculated on 5 root hood cells and each cell was counted for 3 repetitions. The data obtained were analyzed by one way Anova analysis with SPSS. The research results showed that there were differences in ploidy levels of Diplazium esculentum at different altitude indicated by F count (126.849) > F table 0,05 (3.885). Diplazium esculentum located at an heights of 500 masl showed the result of diploid cytological type (2n) which has an average number of chromosomes was 62.934; at an heights of 1500 masl indicated the result of triploid cytological type (3n) which has an average number of chromosomes was 80.334; while at an heights of 2500 masl has an average number of chromosomes as much as 106.4 with tetraploid cytological type results (4n). Thus it can be concluded that there is a difference in ploidy level of Diplazium esculentum at each altitude in Semeru Mountain.